Implementasi dan Menejemen Prespektif Kesetaraan Gender dengan Pendidikan Islam - Masyitoh , Dewi; Hidayanti , Denok Mugi (LPPM Universitas PGRI Argopuro Jember, 2024)
Discrimination between women and men sometimes still occurs in the educational environment. The Al-Quran and Hadith state that a pious human being is the most noble, Allah does not look at a person's face, wealth or physical appearance, but rather judges the heart and deeds. Gender equality is the nature of humanity, men and women have their respective roles in continuing their lives, especially rights, equality, justice and freedom. Men and women play equal roles in the domestic and public spheres. The aim of the research is to examine in depth the implementation and management of the concept of gender equality in Islamic education in schools. The research method used was a literature review using primary sources by KH Husein Muhammad with the title Islam, a women-friendly religion, using an interpretative approach, namely an effort to seek clarity or agreement about social or cultural events based on the perspective and experience of the person being studied. The research results show that there is management between the concept of gender equality and Islamic education. Islamic education must be fair based on the principles of human rights (HAM) and democracy. The fair category provides equal opportunities to obtain knowledge/learning for men and women. Democracy provides freedom of responsibility and dignity for one's choices. Its implementation in formal schools no longer differentiates between male and female students in providing/receiving materials, facilities and learning opportunities, they have the same opportunities to learn and gain knowledge. So that the Islamic education curriculum is implemented and management based on gender justice.